Penerapan Tanggung Jawab Mutlak PT. Pupuk Iskandar Muda kepada Masyarakat Korban Pencemaran Lingkungan - Marlia Sastro (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: Article 88 of Law Number 32 Year 1997 on the Protection and Environmental Management governing strict liability. PT PIM is a company that produces urea, in addition, it also produces waste that can pollute the environment. Environmental pollution has been detrimental to the public around the plant, thus PT. PIM must be responsible directly and immediately. Form of strict liability conducted by PT. PIM to the victims of pollution in the form of compensation and treatment. While the efforts undertaken by public law in the settlement of pollution disputes through out of court settlement involving Muspika Dewantara district, while the settlement is done through the courts. The Implementation of Absolute Responsibility of Pupuk Iskandar Muda Ltd. Company on Environmental Pollution Victims